2016
DOI: 10.1128/aem.03088-15
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Previously Developed Geospatial Model That Predicts the Prevalence of Listeria monocytogenes in New York State Produce Fields

Abstract: dTechnological advancements, particularly in the field of geographic information systems (GIS), have made it possible to predict the likelihood of foodborne pathogen contamination in produce production environments using geospatial models. Yet, few studies have examined the validity and robustness of such models. This study was performed to test and refine the rules associated with a previously developed geospatial model that predicts the prevalence of Listeria monocytogenes in produce farms in New York State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…For instance, in their survey of the microbial quality of the South Nation River Basin, Wilkes et al (2009) found a negative association between the likelihood of L. monocytogenes isolation and E. coli levels. While expected, our failure to identify an association between L. monocytogenes isolation and fecal indicators is interesting given the identification of positive associations between L. monocytogenes isolation and sources of human (e.g., campgrounds, wastewater discharge sites) and livestock (e.g., dairy farms) fecal contamination in this and other studies (Watkins and Sleath, 1981;Dijkstra, 1982;Paillard et al, 2005;Lyautey et al, 2007;Odjadjare et al, 2010;Strawn et al, 2013a;Weller et al, 2016). The failure to identify an association between L. monocytogenes and fecal indicators but the identification of an association between L. monocytogenes and sources of fecal contamination may be due to the fact L. monocytogenes is a microbe adapted to living in non-host environments (Vivant et al, 2013) but the FIBs used here are not (Lee et al, 2008;Bae and Wuertz, 2009).…”
Section: Salmonella Isolation and Eaea-stx Codetection Were Associatementioning
confidence: 70%
See 2 more Smart Citations
“…For instance, in their survey of the microbial quality of the South Nation River Basin, Wilkes et al (2009) found a negative association between the likelihood of L. monocytogenes isolation and E. coli levels. While expected, our failure to identify an association between L. monocytogenes isolation and fecal indicators is interesting given the identification of positive associations between L. monocytogenes isolation and sources of human (e.g., campgrounds, wastewater discharge sites) and livestock (e.g., dairy farms) fecal contamination in this and other studies (Watkins and Sleath, 1981;Dijkstra, 1982;Paillard et al, 2005;Lyautey et al, 2007;Odjadjare et al, 2010;Strawn et al, 2013a;Weller et al, 2016). The failure to identify an association between L. monocytogenes and fecal indicators but the identification of an association between L. monocytogenes and sources of fecal contamination may be due to the fact L. monocytogenes is a microbe adapted to living in non-host environments (Vivant et al, 2013) but the FIBs used here are not (Lee et al, 2008;Bae and Wuertz, 2009).…”
Section: Salmonella Isolation and Eaea-stx Codetection Were Associatementioning
confidence: 70%
“…This study is novel due to the diversity of data types used (e.g., weather data, land use data from federal databases, data scraped from Google and government permits, field-collected water quality data), and the computational approaches used to generate these data. For instance, this study calculated flow path distances that account for topography and represent the physical distance a contaminant travels from its source to the sampling site; the Euclidean distance measures used in previous studies (e.g., Strawn et al, 2013a;Weller et al, 2016) do not capture this complexity. However, it is also important to recognize the limitations associated with spatial data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to E. coli, such proximity effects of forest have also been reported for Listeria monocytogenes and other Listeria species. Weller et al (60) found that with a 100m increase in the distance of a sampling site from forests, the likelihood of L. monocytogenes and other Listeria species isolation in croplands decreased by 14% and 16%, respectively.…”
Section: E Coli In a Watershed With High Forest Coverage May Experiementioning
confidence: 99%
“…Eighteen outbreaks were caused by organic foods from 1992 to 2014 in the U.S., 54% of outbreaks occurred from 2010 to 2014, 44% were associated with produce (e.g., alfalfa sprouts, grape tomatoes), and Salmonella spp and E. coli O157:H7 were the most common pathogens (Harvey et al, 2016).The contamination of produce commodities can occur pre-harvest through the application of raw and/or untreated manure, contaminated agricultural water, direct or indirect (e.g., soil-splash events) contact with contaminated soil or deposition of fecal material from domesticated animals and/or wildlife (Ingham et al, 2004;Olaimat and Holley, 2012;Sharma and Reynnells, 2016). Moreover, fresh produce that is consumed raw or with a minimal processing step presents a unique food safety risk due to the absence of a kill step between harvest and consumption (Olaimat and Holley, 2012;Weller et al, 2016). Therefore, it is crucial that raw manure application, compost processing, and application practices be adequate to minimize the risk of potential crop contamination (Cieslak et al, 1993;Natvig et al, 2002).…”
Section: Introductionmentioning
confidence: 99%